Playscapes : furniture toys for educational play in early childhood - Tan, Li Ling (Nanyang Technological University, 2020)
The introduction of technology is taking over traditional play in children’s early years; it is very common to see children as young as two being offered and engaged with an iPad to keep them occupied. While we cannot deny the benefits of technology and the rapid requirement to be tech savvy as a new literacy in our world, parents and caregivers urgently need to understand that excessive exposure in a child’s early years has multiple adverse effects that may be snowballed later in life. Due to early and excessive use of digital devices in early childhood, an increasing number of children have shown signs of short attention spans, poor short term memory, issues with fine motor skills due to lack of physical activity etc. (based on accounts from childhood educators and doctors in child development). (Swing, E. L., Gentile, D. A., Anderson, C. A., & Walsh, D. A, 2010). The early childhood years are a crucial stage in a child’s life where lifelong cognitive development has to be nurtured and developed. The absence of traditional physical play and key play patterns such as role-playing in early childhood deprive children from developing essential socioemotional skills, aesthetic and creative expression skills, communication (language and literacy) skills, and motor skills. (Hughes, F. P, 2010). Hence, it is vital that young children are constantly able to partake in interactive traditional play in their early childhood to nurture their motor (fine and gross), cognitive, emotional, social, and communicative skills and developmental domains, which can be achieved from engaging in their distinct play pattern: role-playing (Hughes, F. P, 2010). Playscapes is a set of mutable furniture designed for use in small homes that can be repurposed to form many permutations of archetypes or scenarios for young children to utilise and partake in their imaginative world of make-believe through role-playing. Furniture toys are another scale of architecture. They will allow the child to experience their role-play as part of their environment while allowing existing toys to be repurposed in Playscapes to enhance their role-play.